Collective efficacy, self-efficacy, and socio-occupational wellbeing: a quasi-experimental study on an intervention based on the development of collective competences in a blended-learning context - Campos, María Lourdes; Bascur, Axel (Frontiers in Psychology, 2025)
BackgroundAlthough innovation in the workplace seeks to improve the productivity and quality of life of members of organizations, the evidence of a low adoption of new strategies and technologies in companies highlights the need to find effective methods for the implementation of these strategies. In this context, the objective of our study is to verify the effect of an intervention with a blended- learning strategy, with a focus on the development of collective competencies, on the variables of self-efficacy, collective efficacy and socio-occupational wellbeing.MethodWe employed a quasi-experimental pre-test/post-test design. The study variables were evaluated using a non-probability, purposive sample of 110 workers of a Chilean mining company. The intervention group was composed of voluntary participants, same as the control group, who only completed the evaluations. The intervention was conducted over a four-month period, and consisted in 5 in-person training workshops, in parallel with a complementary, continuously open online courses. The content of the training program focused on improving collective management, group synergy, collaborative problem-solving and communicative strategies.ResultsThe analysis shows that the collective competences intervention with the blended-learning program had a positive effect on the variables of self-efficacy, collective efficacy, and socio-occupational wellbeing and associated dimensions from the quasi-experimental group.ConclusionThe results of this study suggest that intervention based on the development of collective competences in a blended-learning context have a positive impact in the self-efficacy, collective efficacy and the social wellbeing on workers in the occupational context.